2020
DOI: 10.1111/ivb.12279
|View full text |Cite
|
Sign up to set email alerts
|

Male morphotypes of the freshwater prawn Macrobrachium brasiliense (Decapoda: Caridea: Palaemonidae)

Abstract: Some decapod species have intraspecific morphological variations that result in distinct adult morphotypes that influence the population structure, social dominance, and reproduction of the population. Here we investigated whether this differentiation into morphotypes occurs in adult males of Macrobrachium brasiliense, through the analysis of relative growth and morphology. Specimens were collected in the region of Uberlândia, Minas Gerais state, southeastern Brazil. Seven dimensions of each male were measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…For many decapods, the smallest cheliped is used for food capture and grooming, while the biggest plays an important role in agonistic, social and reproductive behaviour (Mariappan et al, 2000). As the biggest second pereiopod, the major cheliped length (P2L) and its propodus length (P2PL) were the variables with greater contributions in the PCA analysis in the present study, these dimensions separated the three morphotypes, corroborating the findings of previous studies (Moraes‐Riodades & Valenti, 2004; Nogueira et al, 2020; Pantaleão et al, 2014) with Macrobrachium male morphotypes.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…For many decapods, the smallest cheliped is used for food capture and grooming, while the biggest plays an important role in agonistic, social and reproductive behaviour (Mariappan et al, 2000). As the biggest second pereiopod, the major cheliped length (P2L) and its propodus length (P2PL) were the variables with greater contributions in the PCA analysis in the present study, these dimensions separated the three morphotypes, corroborating the findings of previous studies (Moraes‐Riodades & Valenti, 2004; Nogueira et al, 2020; Pantaleão et al, 2014) with Macrobrachium male morphotypes.…”
Section: Discussionsupporting
confidence: 92%
“…The presence of male morphotypes was observed in approximately 24 world species of Macrobrachium (see the revision of Karplus & Barki, 2019), including some representatives from the neotropical regions independently of the life cycle pattern, that is abbreviated larval development (ALD) or extended larval development (ELD) (for details and definitions see Anger, 2013; Pereira & Garcia, 1995). To cite, Macrobrachium brasiliense that has ALD pattern (Nogueira et al, 2020), and M. rosenbergii , M. amazonicum and M. acanthurus that have ELD pattern (Kuris et al, 1987; Moraes‐Riodades & Valenti, 2004; Pantaleão et al, 2014; Rios et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lack of a laterality pattern seems to be a common feature in Macrobrachium species that have heterochely, this was also observed in Macrobrachium olfersii (Wiegmann, 1836) by Mossolin and Bueno (2003), and in Macrobrachium brasiliense (Heller, 1862) by Nogueira et al (2020), where the males and females analyzed did not have a constant between which propodus (left or right) would be the most developed. Therefore, it has been suggested that this characteristic (i.e., laterality) may not be genetically predetermined (Mossolin and Bueno, 2003).…”
Section: Biology Of the Shrimp Macrobrachium Candangomentioning
confidence: 82%